Personlighetstyper och stressrespons hos djur – med fokus på hund och häst - Maleki, Kimia (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2013)
Animals living in captivity are often subjected to various kinds of stress. Individuals within species can respond differently to the same stressor depending on differences in coping style and physiology. Active and passive coping is a common way to describe different coping styles in animals and it is likely that these strategies have a high heritability. Individuals with an active coping style are characterized by an urge of control and a higher level of aggression than individuals with passive coping style, who in general are more flexible and respond to stress by immobilisation to a greater extent. The aim of this bachelor’s thesis is to investigate the presence of different coping styles and personality types in dogs (Canis lupus familiaris) and horses (Equus ferus caballus) and to find fields of application for this information. Little research has been done to investigate active and passive coping in dogs and horses, which is why more research in the area is needed. Many authors suggest that individuals with an active coping style are more liable to develop stereotypies than individuals with a passive coping style. Knowledge about individual differences regarding personality type and coping in animals can be used in the breeding of dogs and horses and also for predicting behavioural problems in these animals.